Tíos en apuros: un blog en instagram sobre la relación de tíos y sobrinos para millennials de Lima Metropolitana - Leguia Oporto, Yvonne Elisabel (2021)
This project consists of creating an Instagram blog about the relationship between uncles and nephews for Millennials in Lima Metropolitana. The objective of this work is to get Tíos en Apuros in the Top 5 of the most influential care and entertainment blogs for nephews by June 2021. With this, different digital dissemination strategies were proposed, obtaining a production of homemade content, but of quality, which responded to the insights of the target audience. The virtual tool used for this blog is the social network Instagram, because the target audience with which they work is millennial men and women. It was determined to use this medium due to the study carried out by We are Social and Hootsuite, where they detail in the box Instagram Audience Overview that although women lead this network, now more men are joining this virtual space.